The Influence of Gamification Techniques on Students’ Learning Performance and Motivation in Learning: An Experimental Study - Baso Intang Sappaile; Shanshan Xu; Markus Oci; Murphy Xavier; Chandra Halim (Yayasan Adra Karima Hubbi, 2024)
Innovative and engaging learning is becoming increasingly important in modern education. Gamification techniques, which adapt game elements to learning contexts, have attracted research interest as a potentially effective approach to improving student achievement and learning motivation. This research aims to evaluate the effect of gamification techniques on student achievement and motivation in learning. This research method uses an experimental approach with a randomized controlled design, involving two groups of students: an experimental group that applies gamification techniques and a control group that follows conventional learning. Data was collected through achievement tests, learning motivation questionnaires, and classroom observations. The results of this study explain that data analysis shows that students who were involved in learning using gamification techniques had significantly higher achievement than the control group. In addition, students’ learning motivation in the experimental group was also significantly higher than that in the control group. Classroom observations showed higher levels of engagement and participation from students in lessons that used gamification techniques. The conclusion of this research supports the idea that the use of gamification techniques in learning has a positive impact on student achievement and learning motivation. This shows the potential of gamification techniques as an effective tool in increasing the efficiency and effectiveness of learning. The practical implication of this research is that the gamification approach can be integrated into curriculum design to create a more interesting and encouraging learning environment for students. It is hoped that this research can further explore specific aspects of implementing gamification techniques in different educational contexts